The Significance of Responsible Leadership for Innovative Work Behaviour: Conceptual Framework - Soukupová, Nikola; Kotková Stříteská, Michaela (Academic Conferences International Limited, 2024)
Responsible leadership is a key foundation in today's dynamic business world, where the call for ethical behaviour and innovation is louder than ever. Unlike traditional leadership paradigms, responsible leadership represents a multifaceted relationship and views leadership as a dynamic interplay between leaders and stakeholders, rather than a one-sided leader-follower dynamic. Based on this understanding, our study developed a conceptual framework for the relationship between accountable leadership and innovative work behaviors. It also identified mediating-moderating roles to better understand the linkages and gaps in the research. The conceptual framework was developed based on a literature search of 82 studies. The individual constructs of the model were analysed with the findings of other studies and the theoretical and practical contribution was identified through synthesis. In order to create a sustainable future, it is imperative that the pursuit of continuous innovation and the principles of responsible behaviour form the cornerstones of any society. Responsible leadership stimulates innovative work behaviour not only for the benefit of the organisation but also for the well-being of all stakeholders. This is essential to building the relationships and corporate culture that mediate this relationship. The moderator of this relationship is the moral intelligence of the responsible leader, which strengthens the relationship between responsible leadership and innovative work behaviour. The study contributes by providing a comprehensive review of the existing knowledge on responsible leadership and innovative work behavior. Furthermore, it enriches scholarly knowledge and offers practical insights into the characteristics desirable in CEOs to promote responsible and innovative business behavior.
Význam odpovědného vedení pro inovativní pracovní chování: Koncepční rámec
Keywords: Responsible Leadership; Innovative Work Behaviour; Conceptual Framework; Moral Intelligence; Corporate culture; building relationships; mediation role; moderation role; Odpovědné vedení; inovativní pracovní chování; koncepční rámec; morální inteligence; firemní kultura; budování vztahů; role zprostředkovatele; role moderátora.